THE RELATIONSHIP BETWEEN STUDENT PERCEPTION ABOUT PRACTICAL FACILITIES WITH STUDENT LEARNING ACHIEVEMENT FOR THE SUBJECT MAINTENANCE/ SERVICE ENGINE AND ITS COMPONENTS IN THE ELEVENTH GRADE CLASS OF TKR SMK KARSA MULYA PALANGKA RAYA IN ACADEMIC YEAR 2016/ - Adi Sujarwo; Debora (Jurusan Pendidikan Teknologi Dan Kejuruan, 2018)
This study aims to determine the relationship between students' perceptions of practical facilities with student achievement on the subjects of maintenance/service engine and its components in class XI TKR SMK Karsa Mulya Palangka Raya academic year 2016/2017. This research is a quantitative research with correlational approach, and conducted in SMK Karsa Mulya Palangka Raya Class XI Light Vehicle Engineering with total sample of 30 students, with sampling using purposive sampling technique. Instrument of student perception about practice facility before doing research conducted instrument test at SMKN 1 Palangka Raya with the number of respondents counted 32 students. Method of data retrieval used in this research is by using questionnaire instrument for student perception variable about practice facility and documentation of student report value of odd semester with subject of maintenance/service engine and its component for student achievement variable. Test the prerequisite analysis by using the normality test and linearity test. Normality test data obtained that the students' perception data about the practice facilities and student achievement is normally distributed. The test was performed with the help of computer application program SPSS Statistics 17.0 for windows. The results showed that there is a positive and significant relationship between students' perceptions of practical facilities with student achievement in the subjects of maintenance / service engine and its components in class XI TKR SMK Karsa Mulya Palangka Raya Academic Year 2016/2017. This is based on the analysis result shows that the price of r hitung correlation coefficient is 0,648 > r table, at 5% significance level equal to 0,374 or 1% equal to 0,478, and t count equal to 4,503 (ttable 5% = 2,048 < t count = 4,503). In addition, it is known that the contribution of practical facilities to student achievement in grade XI SMK Karsa Mulya Palangka Raya at academic year 2016/2017 by 42%, while 58% is determined by other factors.